AME: A Cross-Scale Constellation of CubeSats to Explore Magnetic Reconnection in the Solar–Terrestrial Relation - Dai, Lei; Wang, Chi; Cai, Zhiming; Gonzalez, Walter; Hesse, Michael; Escoubet, Philippe; Phan, Tai; Vasyliunas, Vytenis; Lu, Quanming; Li, Lei; Kong, Linggao; Dunlop, Malcolm; et al. (Frontiers in Physics, 2020)
A major subset of solar-terrestrial relations, responsible in particular for the driver of space weather phenomena, is the interaction between the Earth’s magnetosphere and the solar wind. As one of the most important modes of the solar-wind-magnetosphere interaction, magnetic reconnection regulates the energy transport and energy release in the solar-terrestrial relation. In-situ measurements in the near-Earth space are crucial for understanding magnetic reconnection. Past and existing spacecraft constellation missions mainly focus on the measurement of reconnection on plasma kinetic-scales. Resolving the macro-scale and cross-scale aspects of magnetic reconnection is necessary for accurate assessment and predictions of its role in the context of space weather. Here, we propose the AME (self Adaptive Magnetic reconnection Explorer) mission consisting of a cross-scale constellation of 12+ CubeSats and one mother satellite. Each CubeSat is equipped with instruments to measure magnetic fields and thermal plasmas particles. With multiple CubeSats, the AME constellation is intended to make simultaneous measurements at multiple scales, capable of exploring cross-scale plasma processes ranging from kinetic-scales to macro-scale.